Judy Moody Predicts the Future [Dada Nálada predpovedá budúcnosť anglicky] / Book 4. - McDonald, Megan 1959- (Walker Books Ltd, 2019)
Judy Moody has a mood for every occasion, and now she has a mood ring to prove it! Judy's mood ring has extra special powers which have put her in a predicting mood, and her outrageous predictions have everyone wondering if she really is psychic.